Development of Rb fountain clock for time keeping - Weiliang, Chen; Fang, Fang; Kun, Liu; Fasong, Zheng; Shaoyang, Dai; Yani, Zuo; Tianchu, Li (Frontiers in Physics, 2022)
A new Rb fountain clock was built at the National Institute of Metrology with the aim to realize robustness and excellent long-term instability for time keeping. While some basic designs have been adopted from our Cs fountain clocks, new features have been included for improved performance. A double-metal interrogation microwave cavity with a thermal expansion self-compensating mechanism was used to reduce the clock sensitivity to temperature fluctuations for the first time, to our knowledge. Moreover, a compact optical system was developed to ensure robustness. These features dramatically increased the ambient temperature range. The developed Rb fountain clock achieved a typical fractional frequency instability of within 10 days of continuous operation without any intervention, demonstrating the potential for time keeping